2009
DOI: 10.1002/ajh.21337
|View full text |Cite
|
Sign up to set email alerts
|

Absolute lymphocyte count at the time of first relapse predicts survival in patients with diffuse large B‐cell lymphoma

Abstract: Peripheral blood absolute lymphocyte count (ALC) is a survival prognostic factor in hematological malignancies. No reports have addressed whether ALC at the time of first relapse (ALC-R) predicts survival. Thus, we assessed the prognostic significance of ALC-R in diffuse large B-cell lymphoma (DLBCL). Patients were required to have been diagnosed with first relapsed DLBCL, have ALC-R values, and to be followed at Mayo Clinic, Rochester. From Feb 1987 until March 2006, 97 first relapsed DLBCL patients qualified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 18 publications
2
39
1
Order By: Relevance
“…It was found that the systemic inflammatory response was associated with poor outcomes in various diseases. For various solid tumors, as well as for lymphomas, inflammation parameters such as WBC, ANC, ALC, and CRP have been associated with higher mortality rates (41)(42)(43)(44)(45)(46). Our results are in accordance with findings on the important roles of inflammation and malnutrition in tumor progression.…”
Section: Discussionsupporting
confidence: 91%
“…It was found that the systemic inflammatory response was associated with poor outcomes in various diseases. For various solid tumors, as well as for lymphomas, inflammation parameters such as WBC, ANC, ALC, and CRP have been associated with higher mortality rates (41)(42)(43)(44)(45)(46). Our results are in accordance with findings on the important roles of inflammation and malnutrition in tumor progression.…”
Section: Discussionsupporting
confidence: 91%
“…Whether this observation may be explained by tumor-mediated suppression of nonmalignant T cells, diminished thymic output of naïve T cells and compensatory homeostatic expansion of oligoclonal peripheral T cells, or some other mechanism, is unknown [47]. As lymphopenia is an adverse prognostic factor in many hematologic malignancies [59][60][61][62][63][64], and undoubtedly contributes to the infectious complications observed in CTCL, improved understanding of the causative mechanism(s) leading to this dramatic loss of T-cell diversity may have significant therapeutic implications.…”
Section: Immunopathogenesismentioning
confidence: 99%
“…[15][16][17][18] Furthermore, the absolute lymphocyte count at the time of first relapse from large cell lymphoma predicted subsequent progression-free and OS. 19 Our objective has been to develop a strategy for inducing an effective antitumor immune response during the posttransplantation period to control or eliminate residual disease. In theory, the posttransplantation phase should be highly amenable to the application of immunotherapy because of a lower tumor burden.…”
Section: Introductionmentioning
confidence: 99%